2015
DOI: 10.1103/physrevlett.114.233602
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Assisted Speed-up of the Field Evolution in Cavity Quantum Electrodynamics

Abstract: We measure the quantum speed of the state evolution of the field in a weakly-driven optical cavity QED system. To this end, the mode of the electromagnetic field is considered as a quantum system of interest with a preferential coupling to a tunable environment: the atoms. By controlling the environment, i.e., changing the number of atoms coupled to the optical cavity mode, an environment assisted speed-up is realized: the quantum speed of the state re-population in the optical cavity increases with the coupli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 37 publications
5
110
0
2
Order By: Relevance
“…In quantum dots, phonon-assisted decoherence was minimized [177,178]. Interestingly, presence of the environment may improve the quantum speed limit [179,180]. This has not yet been explored systematically but could be done, using quantum optimal control.…”
Section: B Fighting and Avoiding Decoherencementioning
confidence: 99%
“…In quantum dots, phonon-assisted decoherence was minimized [177,178]. Interestingly, presence of the environment may improve the quantum speed limit [179,180]. This has not yet been explored systematically but could be done, using quantum optimal control.…”
Section: B Fighting and Avoiding Decoherencementioning
confidence: 99%
“…Traditional realizations of cavity QED in atomic physics [1] have recently been extended to numerous solid state applications, including superconductors [2], spins of defects and quantum dots [3] and fiber optics [4]. One of the most fundamental models in cavity QED is the Tavis-Cummings model [5] that describes coupling of N s two-level systems, which we will call spins for simplicity, to a single optical cavity mode and an external field.…”
Section: Introductionmentioning
confidence: 99%
“…The model (1) conserves the number of excitations, i.e. the Hamiltonian commutes with the operator of the number of bosons plus the number of spins up:…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is found that the non-Markovian evolution induced by the memory effect of environment can accelerate the quantum evolution13141516. A good example of this is the situation where an atom is coupled to a leaky single mode cavity13.…”
mentioning
confidence: 99%